2006
DOI: 10.1007/s11581-006-0002-x
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen and oxygen generation with polymer electrolyte membrane (PEM)-based electrolytic technology

Abstract: With dwindling liquid fuel resources, hydrogen offers a credible alternative. The use of hydrogen in a fuel cell offers the highest fuel conversion efficiency compared with all other technologies and it also has the potential to substantially reduce greenhouse gas and particulate emissions at least at the end-user sites. One of the major barriers to the introduction of the hydrogen economy and its wider acceptance is the lack of the rather costly hydrogen generation, transportation and distribution infrastruct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
48
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(50 citation statements)
references
References 6 publications
2
48
0
Order By: Relevance
“…The differences between predictions and the experimental data are hypothesized to be due to lack of consideration for other significant mass transfer limitation sources or inapplicability of fuel cell operating parameters such as the electroosmotic drag coefficient. Experiments with an anode liquid water feed with a similar cell showed that the current density was not limited by mass transfer up to 1.8 V. At 1.8 V, the current density was 800 mA/cm 2 …”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The differences between predictions and the experimental data are hypothesized to be due to lack of consideration for other significant mass transfer limitation sources or inapplicability of fuel cell operating parameters such as the electroosmotic drag coefficient. Experiments with an anode liquid water feed with a similar cell showed that the current density was not limited by mass transfer up to 1.8 V. At 1.8 V, the current density was 800 mA/cm 2 …”
Section: Discussionmentioning
confidence: 97%
“…These units have the advantages of producing high purity hydrogen (99.999%) at high conversion efficiency (95%). Fast response time as well the ability to accept variations in load make the technology desirable for on-demand delivery and photovoltaic power sources [2]. Disadvantages of operation include high capital cost and the hydrogen production costs being largely dependent on the cost of electricity.…”
mentioning
confidence: 99%
“…These compounds have a great reducing effect on the overvoltage value of an electrolyzer 16 . They improve the ionic conductivity aqueous electrolyte compounds.…”
Section: Effect Of Electrolyte Concentrationmentioning
confidence: 99%
“…Water electrolysis based on catalyst-coated NafionÒ-type sulfonated tetrafluoroethylene based fluoropolymer-copolymer proton exchange membranes (PEMs) is well-characterized both experimentally and operationally, being in essence the operational reverse of a PEM-based H 2 /O 2 fuel cell. [2][3][4][5][6][7][8]14 However, little work has been reported to date on the use of gaseous water vapor as the feedstock to such electrolyzers. 15,16 Sawada et al have demonstrated the feasibility of the concept, 16 but have not elucidated the effects of relative humidity (RH) or ambient temperature conditions on the performance of the electrolyzer.…”
mentioning
confidence: 99%